HUKUM DAN KEPENTINGAN MASYARAKAT (Memosisikan Hukum Sebagai Penyeimbang Kepentingan Masyarakat) - Eman Sulaiman (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2018)
Although Indonesia is a rule of law and has entered the reform era for twenty years, the law has not taken sides with the interests of the people. The law is still full of the interests of certain parties such as authorities and businessmen. This can be seen from the legislation products for national scale and local regulations for local scale. Reformation of law enforcement officials is slow compared to reforms of legal substance. This causes the law to not act as a counterweight to the interests of the community in an effort to realize justice and truth.